PCSK9 post-transcriptional regulation: Role of a 3′UTR microRNA-binding site variant in linkage disequilibrium with c.1420G. (December 2020) - Decourt, Charlotte; Janin, Alexandre; Moindrot, Marine; Chatron, Nicolas; Nony, Séverine; Muntaner, Manon; Dumont, Sabrina; Divry, Eléonore; Dauchet, Luc; Meirhaeghe, Aline; Marmontel, Oriane; Bardel, Claire; et al.
Abstract: Background and aims: Proprotein convertase subtilisin/kexin type 9 (PCSK9) plays a crucial role in cholesterol homeostasis. A common variant, the G allele in position c.1420 (c.1420G), has been associated with a decrease of both plasma PCSK9 and LDL-cholesterol concentrations. However, the functional effect of this variant is currently not well understood. We hypothesized that it could be explained by functional variants in linkage disequilibrium (LD), more specifically, by variants located in the PCSK9 3′ UTR as targets for miR regulation of PCSK9 expression. Methods: Variations in LD with c.1420G were studied in 1029 patients followed for dyslipidaemia . In silico studies identified potential miRNA binding sites induced by PCSK9 3′UTR variants in LD with c.1420G. Their functionality was studied with a luciferase reporter assay in HuH-7  cells and confirmed by cotransfection of anti-miRNAs. Results: The c.*571C and c.*234T variants located in the PCSK9 3′UTR were found in tight LD with c.1420G (D' = 0.962; LOD = 163.06). The haplotype carrying c.*571C showed a 6.7% decrease in luciferase activity ( p  = 0.003). Inhibition of hsa-miR-1228-3p and hsa-miR-143-5p counteracted their effect on the haplotype carrying c.*571C allele, suggesting that PCSK9 expression was decreased by the endogenous binding of hsa-miR-1228-3p and hsa-miR-143-5p on its 3′UTR. Conclusions: This post-transcriptional regulation might contribute towards the association between plasma PCSK9 levels and c.1420G. Such regulation of PCSK9 expression may open new perspectives for the treatment of hypercholesterolemia and atherosclerosis cardiovascular diseases. Graphical abstract: Image 1 . Highlights: PCSK9 plays a crucial role in cholesterol homeostasis and cardiovascular diseases. PCSK9 c.1420G hypocholesterolemic allele is in linkage disequilibrium with c.*571C. PCSK9 3′UTR variant c.*571C creates an illegitimate and functional miR binding site. 3′UTR PCSK9 post-transcriptional regulation could explain the c.1420G LoF effect. This post-transcriptional regulation may open new therapeutic perspectives.